Solar House Ribbon Cutting - Crowder College (2003)
An official dedication ceremony at the house's permanent site on the Crowder College campus took place October 10, 2003. Majority Whip Roy Blunt helped cut the ribbon alongside the Eberle family and other honored students and faculty members.